Prophetic vs Archetypal Plot : comparing Muhammad: the messenger of god ( 2015 ) and star wars prequel trilogy - Shadra Izza Azhari (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1